(3af GdNHQ GdUMaj (B:s (3OQGSI fXQjI h JWHjbjI (B/s - (3QHjY, YHO GdLhGO SYjO eMeOs ((3GdbGgQI (B:s (3OGQ GdaLQ ddfTQ h GdJhRjY ,s, 2005)
(3JfGhd g(B>(3G GdcJGH eaghe GdUMGaI h Gdaf GdUMaj Ke GdNHQ GdUMaj h GfhGYg h eUGOQg Ke GdGTcGd GdUMajI ddeGOI GdNHQjI aj GdUMa ShGA jhejI Gh GSHhYjI Ke HYO (B>(3dc YOI feG(B>(3L JWHjbjI eMGhdG Hjf GdHYO h GdeONd GdfXQjs
Keywords: (3GdNHQs; (3GdUMGaIs